Weaving Architecture Effects on Mechanical and Chemical Performance of Alkali-Treated Coconut Fiber Composites - Agus Choirul Arifin; Deni Nur Fauzi; Noorsakti Wahyudi; Agus Susanto; Pradhana Kurniawan; Yoga Ahdiat Fakhrudi; M. Shafwallah Al. Aziz (Politeknik Piksi Ganesha Indonesia, 2026)
This study examines the effect of fabric architecture and alkali treatment on the properties of coconut fiber–polyester composites as an alternative environmentally friendly material. Coconut fibers were treated with 15% NaOH for 2 hours and woven in basket weave and twill weave patterns. The composites were made using a vacuum-assisted resin infusion method with a fiber fraction of 40%, and compared with E-glass composites as a control. FTIR analysis showed a decrease in the intensity of the absorption band in the range of 1200–1300 cm⁻¹, indicating a reduction in lignin content after alkali treatment. The mechanical test results showed that the basket weave composite had higher tensile and flexural strengths, respectively, of 20.40 N/mm² and 78.45 N/mm², compared to the twill weave at 12.98 N/mm² and 52.31 N/mm². However, the highest impact resistance was obtained in the twill weave at 23.61 J/mm². The results of the study indicate that the weave architecture has a significant effect on the mechanical performance of the composite and has the potential to support the development of sustainable composite materials for engineering applications.